Method for detecting electrolyte consumption in battery and method for optimizing electrolyte formulation
By drawing the porosity-conductivity standard curve and disassembly of aging batteries, the electrolyte consumption of lithium batteries was calculated, and the problem of inaccurate detection in the existing technology was solved, and the accurate measurement of electrolyte consumption and electrolyte formulation were achieved. optimization.
Patent Information
- Application Number
- CN202411124082.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-16
AI Technical Summary
The prior art has inaccuracy in detecting the consumption of lithium battery electrolyte, especially the internal standard dispersion is uneven, the volatility and errors are large during centrifugation, and it cannot be applied to batteries without free electrolyte, and the test results are present. deviation.
By drawing the porosity-conductivity standard curve of the electrode sheet, combining the disassembly and conductivity test of aging batteries, the electrolyte consumption is calculated to avoid uneven internal standard substances and errors during heating. It is suitable for lithium-ion batteries and sodium Ion battery.
It realizes accurate detection of electrolyte consumption, simple and fast operation, reduces testing costs and errors, and is suitable for electrolyte distribution evaluation of fresh and aged batteries.
Smart Images

Figure CN118670957B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrolyte analysis, and specifically to a method for detecting electrolyte consumption in a battery and a method for optimizing an electrolyte formulation. Background Art
[0002] Lithium battery electrolyte is an ion transport carrier in the battery. It is composed of lithium salt, organic solvent, and a small amount of additives. The electrolyte plays the role of conducting ions between the positive and negative electrodes of the lithium battery. It is the guarantee for lithium-ion batteries to obtain advantages such as high voltage and high specific energy. The influence of electrolyte on battery reliability is crucial. It is necessary to study the mechanism of action of electrolyte in lithium batteries, optimize the electrolyte formula, and then improve the performance of the battery cell. In actual application, the amount of electrolyte in lithium-ion batteries is not constant. As the operating conditions are running, the electrolyte is constantly consumed. When the electrolyte is consumed to a certain value, the battery capacity will decay faster, affecting the battery life performance. It can be seen that the electrolyte consumption is very important for electrolyte design and is an important factor affecting battery life reliability. Therefore, the study of electrolyte consumption can optimize the electrolyte formula and identify the risk of battery liquid shortage.
[0003] At present, patents CN105449297 A and CN110994057 A report a quantitative analysis method for electrolyte consumption, which adds an internal standard to the battery and obtains the electrolyte consumption by the content of the internal standard. However, this method easily leads to uneven dispersion of the internal standard, centrifugation cannot ensure that the electrolyte is completely separated, and there is volatilization of the electrolyte organic solvent during the centrifugation process. These factors affect the accuracy of the obtained results.
[0004] Patent CN109088108A reports a quantitative analysis method for lithium-ion battery electrolyte consumption, which obtains electrolyte consumption by heating and volatilizing the solvent and measuring the mass change before and after weighing. However, this method is affected by the accuracy of the balance and reactions such as SEI decomposition during the heating process, resulting in large errors.
[0005] The existing electrolyte consumption calculation method also uses the IC-GC combined determination method, but this method is only suitable for the consumption of free electrolyte and is not applicable to batteries without free electrolyte. There are also some methods that obtain electrolyte consumption through pole piece extraction, centrifugation and other methods, but this method cannot extract evenly and centrifuge completely, resulting in a certain deviation in the test results.
[0006] Therefore, it is necessary to develop a more convenient, accurate and effective method to quantitatively analyze the electrolyte consumption during battery charging and discharging. Summary of the invention
[0007] In view of this, the present invention provides a method for detecting the consumption of electrolyte in a battery and a method for optimizing the electrolyte formula. The detection method is simple and quick to operate, and the test result is more accurate.
[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0009] In a first aspect, the present invention provides a method for detecting electrolyte consumption in a battery, comprising the following steps:
[0010] S1, draw a porosity-conductivity standard curve based on the conductivity of the electrolyte salt in the electrode;
[0011] S2, disassembling the first BOL battery in an empty state to obtain a first free electrolyte, a first positive electrode sheet, and a first negative electrode sheet;
[0012] Testing the electrical conductivity of the first positive electrode sheet and the first negative electrode sheet;
[0013] S3, performing an aging process on the second BOL battery to obtain an aged battery;
[0014] Disassembling the aged battery in an empty state to obtain a second free electrolyte, a second positive electrode sheet and a second negative electrode sheet;
[0015] Testing the conductivity of the second positive electrode sheet and the second negative electrode sheet;
[0016] The first BOL battery and the second BOL battery have the same specifications and contain the same test electrolyte;
[0017] Among them, step S1, step S2, and step S3 are executed in no particular order;
[0018] S4, obtaining the porosity of the first positive electrode sheet, the first negative electrode sheet, the second positive electrode sheet, and the second negative electrode sheet according to the porosity-conductivity standard curve obtained in step S1, the conductivity corresponding to the first positive electrode sheet and the first negative electrode sheet obtained in step S2, and the conductivity corresponding to the second positive electrode sheet and the second negative electrode sheet obtained in step S3;
[0019] The consumption of the test electrolyte is obtained according to the porosity of the first positive electrode sheet, the first negative electrode sheet, the second positive electrode sheet and the second negative electrode sheet, the mass of the first free electrolyte in step S2, the volume of the first positive electrode sheet, the volume of the first negative electrode sheet, the mass of the second free electrolyte in step S3, and the density of the test electrolyte.
[0020] In the embodiment of the present invention, step S1 specifically includes:
[0021] S11, placing at least two electrode pieces with different porosities in a test electrolyte for immersion treatment, and taking out the electrode pieces;
[0022] S12, extracting the electrolyte salt in the electrode to obtain an electrolyte salt solution, testing the conductivity of the electrolyte salt solution, and obtaining the conductivity corresponding to the electrode;
[0023] S13, obtaining a porosity-conductivity standard curve according to the porosity and corresponding conductivity of the electrode.
[0024] Preferably, the soaking time in step S11 is not less than 10 minutes.
[0025] In the embodiment of the present invention, step S12 specifically includes:
[0026] After the organic solvent in the electrode has evaporated, the electrode is completely immersed in an organic extractant, and static treatment and ultrasonic extraction are performed in sequence to obtain an electrolyte salt solution; the conductivity of the electrolyte salt solution at a preset time point is obtained as the conductivity corresponding to the electrode, and the preset time point is 50~70s.
[0027] Preferably, the organic extractant includes at least one of propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC).
[0028] Preferably, both the static treatment and the ultrasonic extraction are carried out in a closed container.
[0029] Preferably, the liquid level of the organic extractant in the sealed container is ≥10 mm.
[0030] Preferably, the mass percentage of the electrode and the organic extractant is 10% to 20%.
[0031] Preferably, the static treatment time is 8 to 24 hours.
[0032] Preferably, the power of ultrasonic extraction is 300-500 W, and the time is 10-40 min.
[0033] In the embodiment of the present invention, the same method as step S12 is used to test the conductivity of the first positive electrode sheet and the first negative electrode sheet, and to test the conductivity of the second positive electrode sheet and the second negative electrode sheet.
[0034] Preferably, the test temperature of the conductivity is 24-26°C.
[0035] Preferably, the aging treatment is carried out at a temperature of 40 to 70° C. and for a time of 100 to 150 days.
[0036] In the embodiment of the present invention, in step S2, the first BOL battery is subjected to a first discharge to obtain a first BOL battery in an empty state.
[0037] In the embodiment of the present invention, in step S3, the aged battery is subjected to a second discharge to obtain an aged battery in an empty state.
[0038] Preferably, the discharge rate of the first discharge or the second discharge is ≤0.05C.
[0039] Preferably, the disassembly is performed in a low-humidity environment.
[0040] Preferably, the dew point of the low humidity environment is ≤ -20°C.
[0041] In an embodiment of the present invention, the battery is a lithium ion battery or a sodium ion battery;
[0042] In an embodiment of the present invention, the electrolyte salt is a lithium salt or a sodium salt.
[0043] In a second aspect, the present invention provides a method for optimizing an electrolyte formulation, comprising the following steps:
[0044] Using the above-mentioned method for detecting the consumption of electrolyte, the consumption of at least two electrolytes with different formulations is detected;
[0045] By comparing the consumption of electrolytes with different formulations, the optimal formulation is screened out.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] The present invention calculates the consumption of electrolyte during the aging process based on the change in the porosity of the positive and negative electrodes during the battery aging process. The method first establishes a porosity-conductivity standard curve, then disassembles the aged battery, takes out the positive and negative electrode plates, soaks the positive and negative electrode plates in a certain organic solvent for extraction, and obtains the positive and negative electrode porosity through the extraction of the organic solvent conductivity, and then calculates the consumption of electrolyte during the battery aging process based on the change in the positive and negative electrode porosity. This method is not only simple and fast to operate, and improves the test efficiency, but also avoids errors caused by uneven internal standards, centrifugation, heating, etc., making the test results more accurate;
[0048] The present invention can test the electrolyte distribution of lithium-ion batteries without using expensive testing instruments, and can be used not only to evaluate the electrolyte infiltration distribution of fresh batteries, but also to evaluate the electrolyte distribution of aged batteries, thus saving a lot of testing costs and labor costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 Electrode conductivity test flow chart.
[0050] Figure 2 Negative electrode porosity-conductivity standard curve.
[0051] Figure 3 Porosity-conductivity standard curve of positive electrode. DETAILED DESCRIPTION
[0052] The present invention discloses a method for detecting the amount of electrolyte consumed in a battery and a method for optimizing the electrolyte formulation. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters for implementation. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0053] Terminology explanation:
[0054] BOL battery refers to a battery at the beginning of life (BOL), that is, a battery that has not yet deteriorated or aged.
[0055] Aging refers to the storage process of the battery after the first charge and formation after the battery is assembled and filled.
[0056] In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes, and do not indicate or imply relative importance.
[0057] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0058] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0059] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0060] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0061] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0062] Specifically, the present invention adopts the following technical solutions:
[0063] In a first aspect, the present invention provides a method for detecting electrolyte consumption in a battery, comprising the following steps:
[0064] S1, draw a porosity-conductivity standard curve based on the conductivity of the electrolyte salt in the electrode;
[0065] S2, disassembling the first BOL battery in an empty state to obtain a first free electrolyte, a first positive electrode sheet, and a first negative electrode sheet;
[0066] Testing the electrical conductivity of the first positive electrode sheet and the first negative electrode sheet;
[0067] S3, performing an aging process on the second BOL battery to obtain an aged battery;
[0068] Disassembling the aged battery in an empty state to obtain a second free electrolyte, a second positive electrode sheet and a second negative electrode sheet;
[0069] Testing the conductivity of the second positive electrode sheet and the second negative electrode sheet;
[0070] The first BOL battery and the second BOL battery have the same specifications and contain the same test electrolyte;
[0071] Among them, step S1, step S2, and step S3 are executed in no particular order;
[0072] S4, obtaining the porosity of the first positive electrode sheet, the first negative electrode sheet, the second positive electrode sheet, and the second negative electrode sheet according to the porosity-conductivity standard curve obtained in step S1, the conductivity corresponding to the first positive electrode sheet and the first negative electrode sheet obtained in step S2, and the conductivity corresponding to the second positive electrode sheet and the second negative electrode sheet obtained in step S3;
[0073] The consumption of the test electrolyte is obtained according to the porosity of the first positive electrode sheet, the first negative electrode sheet, the second positive electrode sheet and the second negative electrode sheet, the mass of the first free electrolyte in step S2, the volume of the first positive electrode sheet, the volume of the first negative electrode sheet, the mass of the second free electrolyte in step S3, and the density of the test electrolyte.
[0074] In the embodiment of the present invention, step S1 specifically includes:
[0075] S11, placing at least two electrode pieces with different porosities in a test electrolyte for immersion treatment, and taking out the electrode pieces;
[0076] S12, extracting the electrolyte salt in the electrode to obtain an electrolyte salt solution, testing the conductivity of the electrolyte salt solution, and obtaining the conductivity corresponding to the electrode;
[0077] S13, obtaining a porosity-conductivity standard curve according to the porosity and corresponding conductivity of the electrode.
[0078] Preferably, the soaking time in step S11 is not less than 10 minutes. Exemplarily, the soaking time is any value among 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, or any value within the range of any two of the above values.
[0079] In the embodiment of the present invention, step S12 specifically includes:
[0080] After the organic solvent in the electrode has evaporated, the electrode is completely immersed in an organic extractant, and static treatment and ultrasonic extraction are performed in sequence to obtain an electrolyte salt solution; the conductivity of the electrolyte salt solution at a preset time point is obtained as the conductivity corresponding to the electrode, and the preset time point is 50~70s.
[0081] In an embodiment of the present invention, when testing the conductivity of the electrolyte salt solution, the conductivity reading will fluctuate at the initial stage, so it is necessary to read the conductivity reading of the stable time period to obtain the conductivity of the electrolyte salt solution at a preset time point. At the same time, the volatilization of the organic extractant is reduced as much as possible to avoid the test error of the conductivity caused by the volatilization of the solvent, and the preset time point is 50 to 70 seconds. Exemplarily, the preset time point is any value among 50 seconds, 52 seconds, 54 seconds, 56 seconds, 58 seconds, 60 seconds, 62 seconds, 64 seconds, 66 seconds, 68 seconds, and 70 seconds, or any value within the range of any two of the above values.
[0082] In order to reduce the conductivity test error, each sample was tested 5 times, the maximum and minimum values were removed, and the average value of the remaining electrode conductivity was taken.
[0083] In the embodiment of the present invention, in step S12, before extracting the electrolyte salt in the electrode, in order to control the volume of the electrode and reduce the amount of organic extractant, the electrode can be cut into a regular shape with a smaller volume, such as a cylinder or a cube with a diameter or side length of 10 to 20 mm. In a specific embodiment, the electrode is cut into a 12 mm cylinder.
[0084] Preferably, the organic extractant includes at least one of propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC).
[0085] In a specific embodiment of the present invention, the organic extractant is propylene carbonate (PC).
[0086] Preferably, both the static treatment and the ultrasonic extraction are carried out in a closed container.
[0087] In order to facilitate the conductivity test and reduce the test error, preferably, the liquid level of the organic extractant in the sealed container is ≥10 mm, exemplified by any value of 10 mm, 15 mm, 20 mm, 25 mm, 30 mm, 35 mm, 40 mm, 45 mm, 50 mm, 55 mm, 60 mm, or any value within the range consisting of any two of the above values.
[0088] In order to facilitate the conductivity test and reduce the test error, preferably, the mass percentage of the electrode and the organic extractant is 10% to 20%, and exemplary values are any value among 10%, 12%, 14%, 16%, 18%, 20%, or any value within the range of any two of the above values.
[0089] Preferably, the static treatment time is 8 to 24 hours, exemplified by any value among 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, and 24 hours, or any value within the range consisting of any two of the above values.
[0090] In order to make the electrolyte salt in the pores of the electrode fully dissolved in the organic extractant, facilitate the subsequent test of conductivity, and avoid stripping the electrode powder, preferably, the power of ultrasonic extraction is 300-500 W, and the time is 10-40 min. Exemplarily, the power of ultrasonic extraction is any value among 300 W, 350 W, 400 W, 450 W, 500 W, or any value within the range of any two of the above values. Exemplarily, the time of ultrasonic extraction is any value among 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, or any value within the range of any two of the above values.
[0091] In order to reduce the volatilization of the organic extractant as much as possible, in an embodiment of the present invention, the same method as step S12 is adopted to test the conductivity corresponding to the first positive electrode sheet and the first negative electrode sheet, and to test the conductivity corresponding to the second positive electrode sheet and the second negative electrode sheet.
[0092] Preferably, the test temperature of the conductivity is 24-26° C. Exemplarily, the test temperature of the conductivity is any value among 24° C., 24.5° C., 25° C., 25.5° C., 26° C., or any value within the range consisting of any two of the above values.
[0093] Preferably, the temperature of the aging treatment is 40-70°C, and the time is 100-150 days. Exemplarily, the temperature of the aging treatment is any value of 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, or any value in the range of any two of the above values. Exemplarily, the time of the aging treatment is any value of 100 days, 110 days, 120 days, 130 days, 140 days, 150 days, or any value in the range of any two of the above values.
[0094] In steps S2 and S3, the battery is in an empty state. There are three considerations: first, the empty state of the battery can ensure the safety of the disassembly operation; second, in battery states other than the empty state, such as the fully charged state, the negative electrode is fully embedded with lithium, and the negative electrode is easy to react with moisture and oxygen in the air to form new lithium salts on the surface of the negative electrode, which makes the test result biased large, while the negative electrode in the empty state is relatively stable; third, in battery states other than the empty state, such as the fully charged state, because the distance between the graphite layers of the negative electrode is embedded with lithium, when cutting the electrode sheet, the edge is easy to fall off, and the consistency of conditions cannot be guaranteed. In addition, the falling of materials will lead to smaller test results.
[0095] In the embodiment of the present invention, in step S2, the first BOL battery is subjected to a first discharge to obtain a first BOL battery in an empty state.
[0096] In the embodiment of the present invention, in step S3, the aged battery is subjected to a second discharge to obtain an aged battery in an empty state.
[0097] Preferably, the discharge rate of the first discharge or the second discharge is ≤0.05 C. Exemplarily, the discharge rate of the first discharge or the second discharge is any value among 0.01 C, 0.02 C, 0.03 C, 0.04 C, 0.05 C, or any value within the range formed by any two of the above values.
[0098] Preferably, the disassembly is performed in a low-humidity environment.
[0099] Preferably, the dew point of the low humidity environment is ≤ -20°C. Exemplarily, the dew point of the low humidity environment is any value among -40°C, -35°C, -30°C, -25°C, -20°C, or any value within a range consisting of any two of the above values.
[0100] In the embodiment of the present invention, step S4 uses the following calculation formula to obtain the consumption of the test electrolyte:
[0101] .
[0102] Wherein, △m represents the consumption of the test electrolyte, m1 represents the mass of the first free electrolyte (in g for example), m2 represents the mass of the second free electrolyte (in g for example), ε 正 represents the porosity of the first positive electrode sheet, ε 正 ’ represents the porosity of the second positive electrode sheet, V 正 Indicates the volume of the first positive electrode plate (unit: cm 3 ), ε 负 represents the porosity of the first negative electrode sheet, ε 负 ’ represents the porosity of the second negative electrode sheet, V 负 Indicates the volume of the first negative electrode plate (unit: cm 3 ), ρ represents the density of the test electrolyte (unit is, for example, g / cm 3 ).
[0103] In an embodiment of the present invention, the battery is a lithium ion battery or a sodium ion battery;
[0104] In an embodiment of the present invention, the electrolyte salt is a lithium salt or a sodium salt.
[0105] In an embodiment of the present invention, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPF2O2), lithium tetrafluorooxalate phosphate (LiPF4C2O4), lithium oxalate phosphate (LiPO2C2O4), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalate borate (LiODFB), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethylsulfonyl imide) (LiTFSI), and lithium bis(fluorosulfonyl imide) (LiFSI);
[0106] In an embodiment of the present invention, the sodium salt includes at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium hexafluoroantimonate (NaSbF6), sodium difluorophosphate (NaPF2O2), sodium 4,5-dicyano-2-trifluoromethylimidazolium (NaDTI), sodium bis(oxalyl)borate (NaBOB), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), and sodium bis(fluorosulfonyl)imide (NaFSI).
[0107] In the embodiment of the present invention, the test electrolyte may or may not include macromolecular organic additives (such as FEC, VC, etc.), which is not limited in the present invention.
[0108] In the embodiment of the present invention, the free electrolyte cannot be completely poured out, and a part of the electrolyte is dispersed on the battery components, and this part of the free electrolyte is difficult to quantify. Therefore, by using the same operation method, the first BOL battery in the empty state is disassembled to separate the first free electrolyte, and the aged battery in the empty state is disassembled to separate the second free electrolyte, the error can be offset.
[0109] In a second aspect, the present invention provides a method for optimizing an electrolyte formulation, comprising the following steps:
[0110] Using the above-mentioned method for detecting the consumption of electrolyte, the consumption of at least two electrolytes with different formulations is detected;
[0111] By comparing the consumption of electrolytes with different formulations, the optimal formulation is screened out.
[0112] The detection principle of the present invention is:
[0113] First, the electrolyte in the battery includes free electrolyte and electrolyte filled in the positive and negative electrode plates and the pores of the diaphragm. During the battery aging process, the generation of byproducts (such as gas, negative electrode electrolyte interface SEI, positive electrode electrolyte interface CEI) will cause electrolyte consumption, and the amount of electrolyte in the battery before and after aging (liquid retention) satisfies the law of conservation of matter. The amount of electrolyte in the battery before and after aging remains unchanged, that is, the sum of the amount of free electrolyte in the battery after aging, the amount of electrolyte in the pores and the consumption of electrolyte is equal to the sum of the amount of free electrolyte in the battery and the amount of electrolyte in the pores before aging. Based on this sum relationship, the calculation formula for electrolyte consumption can be obtained.
[0114] Second, the amount of electrolyte in the pores of the positive and negative electrode plates and the diaphragm is related to the pore size. The inventors found that the pore size and porosity of the positive and negative electrode plates will change during the battery aging process, while the pore size and porosity of the diaphragm remain unchanged. After injection, the pores of the electrode plates need to be fully filled with electrolyte to ensure basic dynamic performance, otherwise the battery cannot be charged and discharged, and the distribution of electrolyte salt in the electrolyte is uniform; the larger the pores of the positive and negative electrode plates, the more electrolyte needs to be filled in the pores of the electrode plates. After the solvent evaporates, the electrolyte salt still exists in the pores, and the more electrolyte salt exists in the electrode plates. Therefore, the pore size or porosity can be reflected by the amount of electrolyte salt, and the electrode plate porosity is linearly related to the electrolyte salt content in the pores.
[0115] Third, since the electrode porosity is related to the electrolyte salt content in the pores, the electrolyte salt content is related to the electrolyte salt concentration, and the electrolyte salt concentration is related to the electrolyte salt conductivity, it can be inferred that the porosity and conductivity are linearly related. The concentration of the electrolyte salt filled in the pores before and after aging remains unchanged. Therefore, the porosity of the electrode before and after aging can be deduced through the porosity-conductivity standard curve, and then the mass of the electrolyte in the pores can be further deduced, and finally the consumption of the electrolyte can be obtained.
[0116] In the present invention, the derivation process of the calculation formula for testing the consumption of electrolyte is as follows:
[0117] The porosity of the diaphragm is ε 隔膜 The volume of the diaphragm in the winding core is V 隔膜 , the pore volume of the electrode or diaphragm = the length of the electrode or diaphragm × width × thickness × number of folds × number of winding cores × porosity = V 极片 or V 隔膜 × Porosity. Before aging, the amount of electrolyte in the battery .
[0118] The porosity of the diaphragm will not change before and after aging; the volume of the electrode or diaphragm in the battery will remain unchanged before and after aging, and the density of the electrolyte will remain unchanged before and after aging.
[0119] After aging, the porosity of the positive and negative electrodes changes due to the expansion of the positive and negative electrodes during charge and discharge, and the thickening of the CEI and SEI on the positive and negative electrodes. .
[0120] The amount of electrolyte in the battery remains unchanged before and after aging. Based on this relationship, the following equation is established:
[0121] ,but,
[0122] .
[0123] The reagents, instruments or materials used in the present invention can be obtained through commercial channels.
[0124] The present invention will be further described below in conjunction with embodiments:
[0125] Example 1
[0126] Soak the electrodes with different porosities in the electrolyte for 30 minutes, take out the electrodes, wait for the solvent to fully evaporate, punch the electrodes into 12mm discs, put the discs into a glass bottle with a diameter of 30mm, add 15mL of propylene carbonate (PC) solvent (liquid level is 53mm, the mass ratio of the electrode to PC is 11.13%), seal and let stand for 12 hours, ultrasonicate at a power of 400W for 30 minutes, put the glass bottle in a 25℃ water bath, and use a conductivity meter to test the conductivity of the electrodes with different porosities (the reading is stable after 60s, and the conductivity reading in the stable time period is read; each sample is tested 5 times, the maximum and minimum values are removed, and the average value of the remaining electrode conductivity is taken), and the standard curve of the porosity-conductivity of the positive and negative electrode electrodes is obtained. See the electrode conductivity test flow chart for details. Figure 1 , the standard curve of positive and negative electrode porosity-conductivity is shown in Figure 2 and Figure 3 .
[0127] The liquid content of the 218Ah battery is 698g. The battery at the beginning of life (BOL) is discharged at 0.05C. The battery is disassembled in a low humidity environment (dew point ≤ –20℃), 177g of free electrolyte is poured out, and the positive and negative pole pieces are taken out. After the solvent evaporates, the pole pieces are punched into 12 mm discs respectively. The discs are placed in a glass bottle with a diameter of 30 mm, and 15 mL of PC solvent is added (the liquid level is 53mm, and the mass ratio of the pole piece to PC is 11.13%). After sealing, it is left to stand for 12h and ultrasonicated for 30 min, put the glass bottle in a 25℃ water bath, and use a conductivity meter to test the conductivity of the positive and negative electrodes (the reading stabilizes after 60s, and the conductivity reading of the stable time period is read; each sample is tested 5 times, the maximum and minimum values are removed, and the average value of the remaining electrode conductivity is taken). The conductivity of the positive and negative electrodes is 11.3μs / cm and 19.85μs / cm respectively, and the corresponding positive and negative electrode sheets have a positive electrode porosity of 21.3% and a negative electrode porosity of 27.4%, of which the diaphragm porosity is 39%. Positive electrode sheet volume V 正 435.7592cm 3 、Volume of negative electrode 负 699.1430cm 3 , diaphragm volume V 隔膜 128.9434cm 3 , the electrolyte density is 1.22g / cm 3 .
[0128] After the 218Ah battery was stored at 60°C for 120 days, the aged battery was discharged at 0.05C, and the battery was disassembled in a low humidity environment (dew point ≤ –20°C). 104g of free electrolyte was poured out, and the positive and negative pole pieces were taken out. After the solvent evaporated, the pole pieces were punched into 12mm discs respectively, and the discs were placed in a glass bottle with a diameter of 30 mm. 15 mL of PC solvent (liquid level was 53mm, and the mass ratio of pole piece to PC was 11.13%) was added, and the bottle was sealed and left to stand for 12h. Ultrasonication was performed for 30 min, put the glass bottle in a 25℃ water bath, and use a conductivity meter to test the conductivity of the positive and negative electrodes respectively (the indication is stable after 60s, and the conductivity indication of the stable time period is read; each sample is tested 5 times, the maximum and minimum values are removed, and the average value of the remaining electrode conductivity is taken). The conductivity of the positive and negative electrodes are 9.48μs / cm and 17.87μs / cm respectively, and the corresponding positive and negative electrode sheets have a positive electrode porosity of 20%, a negative electrode porosity of 26%, and a diaphragm porosity of 39%. It can be seen that the diaphragm porosity and the amount of electrolyte filled in the diaphragm remain unchanged before and after aging.
[0129] The electrolyte consumption △m is calculated by the following formula:
[0130]
[0131] =(177-104)+[(21.3%-20%)×435.7592+(27.4%-26%)×699.143]×1.22
[0132] =91.85 (g).
[0133] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for detecting electrolyte consumption in a battery, characterized in that: The steps include: S1, draw a porosity-conductivity standard curve based on the conductivity of the electrolyte salt in the electrode; S2, disassembling the first BOL battery in an empty state to obtain a first free electrolyte, a first positive electrode sheet, and a first negative electrode sheet; Testing the electrical conductivity of the first positive electrode sheet and the first negative electrode sheet; S3, performing an aging process on the second BOL battery to obtain an aged battery; Disassembling the aged battery in an empty state to obtain a second free electrolyte, a second positive electrode sheet and a second negative electrode sheet; Testing the conductivity of the second positive electrode sheet and the second negative electrode sheet; The first BOL battery and the second BOL battery have the same specifications and contain the same test electrolyte; Among them, step S1, step S2, and step S3 are executed in no particular order; S4, obtaining the porosity of the first positive electrode sheet, the first negative electrode sheet, the second positive electrode sheet, and the second negative electrode sheet according to the porosity-conductivity standard curve obtained in step S1, the conductivity corresponding to the first positive electrode sheet and the first negative electrode sheet obtained in step S2, and the conductivity corresponding to the second positive electrode sheet and the second negative electrode sheet obtained in step S3; Obtaining the consumption of the test electrolyte according to the porosity of the first positive electrode sheet, the first negative electrode sheet, the second positive electrode sheet, and the second negative electrode sheet, the mass of the first free electrolyte in step S2, the volume of the first positive electrode sheet, the volume of the first negative electrode sheet, the mass of the second free electrolyte in step S3, and the density of the test electrolyte; Wherein, step S1 specifically includes: S11, placing at least two electrode pieces with different porosities in a test electrolyte for immersion treatment, and taking out the electrode pieces; S12, extracting the electrolyte salt in the electrode to obtain an electrolyte salt solution, testing the conductivity of the electrolyte salt solution, and obtaining the conductivity corresponding to the electrode; S13, obtaining a porosity-conductivity standard curve according to the porosity and corresponding conductivity of the electrode piece; In step S11, the soaking treatment time is not less than 10 minutes; Step S4 uses the following calculation formula to obtain the consumption of the test electrolyte: Wherein, △m represents the consumption of the test electrolyte, m1 represents the mass of the first free electrolyte, m2 represents the mass of the second free electrolyte, ε 正 represents the porosity of the first positive electrode sheet, ε 正 ’ represents the porosity of the second positive electrode sheet, V 正 represents the volume of the first positive electrode plate, ε 负 represents the porosity of the first negative electrode sheet, ε 负 ’ represents the porosity of the second negative electrode sheet, V 负 represents the volume of the first negative electrode plate, and ρ represents the density of the test electrolyte.
2. The detection method according to claim 1, characterized in that: Step S12 specifically includes: After the organic solvent in the electrode has evaporated, the electrode is completely immersed in an organic extractant, and static treatment and ultrasonic extraction are performed in sequence to obtain an electrolyte salt solution; the conductivity of the electrolyte salt solution at a preset time point is obtained as the conductivity corresponding to the electrode, and the preset time point is 50~70s.
3. The detection method according to claim 2, characterized in that: The organic extractant includes at least one of propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
4. The detection method according to claim 2, characterized in that: The static treatment and the ultrasonic extraction are both carried out in a closed container; The liquid level of the organic extractant in the sealed container is ≥10 mm; The mass percentage of the electrode and the organic extractant is 10% to 20%; The static treatment time is 8 to 24 hours; The power of the ultrasonic extraction is 300-500 W, and the time is 10-40 min.
5. The detection method according to claim 1, characterized in that: The same method as step S12 is used to test the conductivity of the first positive electrode sheet and the first negative electrode sheet, and the conductivity of the second positive electrode sheet and the second negative electrode sheet, wherein the test temperature of the conductivity is 24-26°C.
6. The detection method according to claim 1, characterized in that: The aging treatment is carried out at a temperature of 40 to 70° C. and for a time of 100 to 150 days.
7. The detection method according to claim 1, characterized in that: In step S2, the first BOL battery is subjected to a first discharge to obtain the first BOL battery in an empty state; In step S3, the aged battery is subjected to a second discharge to obtain the aged battery in an empty-power state; The discharge rate of the first discharge or the second discharge is ≤0.05C; The disassembly is performed in a low-humidity environment; The dew point of the low humidity environment is ≤–20°C.
8. The detection method according to any one of claims 1 to 7, characterized in that: The battery is a lithium ion battery or a sodium ion battery; The electrolyte salt is a lithium salt or a sodium salt.
9. A method for optimizing an electrolyte formulation, characterized in that: The steps include: Using the detection method described in any one of claims 1 to 8 to detect the consumption of at least two electrolytes with different formulations; By comparing the consumption of electrolytes of different formulations, the formulation with lower consumption of electrolyte is screened out.
